Changes in the cortisol and oxytocin levels of first-time pregnant women during interaction with an infant: a randomized controlled trial - Nozomi Sonoda; Kaori Takahata; Wataru Tarumi; Kazuyuki Shinohara; Shigeko Horiuchi (BMC, 2021)
Abstract Background During pregnancy, physiological, psychological, and social changes affect pregnant women's childcare anxiety and childrearing behavior. However, there are scarce reports on hormonal evaluation related to such anxiety and behavior. Herein, we evaluated changes in salivary cortisol (primary outcome) and oxytocin (secondary outcome) levels of first-time pregnant women when interacting with an infant and discussed the relation of these changes to the women's stress level. Methods This was a two-arm randomized controlled trial. Participants were randomly assigned using a web-based randomization system. The experimental group involved interaction with an infant for 30 min. The control group involved watching a DVD movie of an infant for 30 min. Saliva samples were collected at preintervention and postintervention. Saliva samples were assayed, and all data were compared between and within the groups using independent t-test and paired t-test with a two-sided 5% significance level. This study was approved by the Research Ethics Committee of St. Luke's International University. Results A total of 102 women were randomly assigned to the experimental (n = 51) and control (n = 51) groups. Finally, 38 women in the experimental group and 42 women in the control group were analyzed. The salivary cortisol level significantly decreased after the interventions in both groups (t = 4.57, p = 0.00; t = 5.01, p = 0.00). However, there were no significant differences in the salivary cortisol (t = 0.349, p = 0.73) and oxytocin (t = − 1.945, p = 0.58) levels between the two groups. Conclusions The salivary cortisol level of first-time pregnant women significantly decreased in the experimental and control groups postintervention, although no significant difference was found between the two groups. Such decrease indicates stress reduction and release among these women. The absence of a significant increase in salivary oxytocin level in both groups may be related to the limitations of an insufficient number of samples that could be analyzed owing to the small saliva volume in some samples and the lack of adequate tactile stimulation of the intervention protocol. These results and procedural limitations provide useful insights into approaching subsequent studies aiming at continuously optimizing detection procedures. Trial registration UMIN000028471 (Clinical Trials Registry of University Hospital Information Network. July 31, 2017- Retrospectively registered.